Metal–Organic Framework Templated Porous Carbon‐Metal Oxide/Reduced Graphene Oxide as Superior Support of Bimetallic Nanoparticles for Efficient Hydrogen Generation from Formic Acid. Issue 1 (1st September 2017) - Song, Fu‐Zhan; Zhu, Qi‐Long; Yang, Xinchun; Zhan, Wen‐Wen; Pachfule, Pradip; Tsumori, Nobuko; Xu, Qiang
Abstract: Ultrafine PdAg nanoparticles (NPs) are successfully immobilized on zirconia/porous carbon/reduced graphene oxide (ZrO2 /C/rGO) nanocomposite derived from metal organic framework/graphene oxide. Monodispersed PdAg NPs (diameter ≤2.5 nm) can be facilely anchored on the ZrO2 /C/rGO and the aggregation of metal NPs can be avoided utmostly. By virtue of the synergistic effect between metal NPs and support, the resulting PdAg@ZrO2 /C/rGO exhibits excellent activity (turnover frequency, 4500 h −1 at 333 K) for the dehydrogenation of formic acid. As an effective strategy, it provides an opportunity to immobilize ultrafine metal NPs on metal oxide/porous carbon/reduced graphene oxide, which has tremendous application prospects in various catalytic fields. Abstract : A superior support, namely ZrO2 /C/rGO derived from metal–organic framework/graphene oxide, to immobilize ultrafine PdAg nanoparticles (NPs) (diameter ≤ 2.5 nm) is reported. By virtue of the synergistic effect between metal NPs and support, the resulting PdAg@ZrO2 /C/rGO nanocatalyst shows extremely high catalytic performance (turnover frequency, 4500 h −1 ) for the dehydrogenation of formic acid.